Rethinking Private Higher Education for Changing Realities - Buckner, Elizabeth (International Higher Education, 2025)
<h3 id="the-rise-of-private-higher-education-has-transformed-the-global-higher-education-landscape-despite-its-expansion-private-higher-education-remains-contentious-often-seen-as-low-quality-and-profit-driven-yet-private-universities-often-fulfill-key-national-goals-expanding-access-supporting-socioeconomic-mobility-or-offering-distinctive-educational-models-this-article-calls-for-deeper-scholarly-engagement-with-private-higher-education-as-a-lens-for-examining-broader-debates-in-higher-education-systems" data-pm-slice="1 1 []">The rise of private higher education has transformed the global higher education landscape. Despite its expansion, private higher education remains contentious, often seen as low-quality and profit-driven. Yet, private universities often fulfill key national goals, expanding access, supporting socioeconomic mobility, or offering distinctive educational models. This article calls for deeper scholarly engagement with private higher education as a lens for examining broader debates in higher education systems.